Exkursionsdidaktik Geographische Bildung in der Grundschule - Gryl, Inga; Kuckuck, Miriam (Verlag Julius Klinkhardt, 2023)
For the multi-perspective (subject) teaching in primary school, the reference to the living world is a central orientation. Field trips are an ideal way to bring the living world into the classroom. This anthology shows fifteen didactic methods for excursions in primary school, which can be transferred to different learning environments and places. Not only classical excursions are realised, but also student-centred as well as media augmented and digital excursions are presented. Each excursion method introduces and applies a guiding didactic principle of geography and science education, so that in addition to the variety of methods, this volume also provides a broad conceptual-didactic orientation.